2015
DOI: 10.1007/s00705-015-2433-z
|View full text |Cite
|
Sign up to set email alerts
|

Association of lipid profile alterations with severe forms of dengue in humans

Abstract: Previous studies have shown a relationship between circulating lipids and dengue virus infection; however, the association of altered lipid profiles with severe dengue remains little studied. The aim of this study was to determine the association between circulating lipid content and severe dengue and/or platelet counts. Ninety-eight patients (2-66 years old) classified as having dengue without warning signs (DNWS), dengue with warning signs (DWWS), or severe dengue (SD) and 62 healthy individuals were studied… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
44
0
7

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(54 citation statements)
references
References 30 publications
3
44
0
7
Order By: Relevance
“…Thrombocyte counts below 50,000 cells/ μ L are considered to be a risk factor for bleeding [25–27]. Recently, a correlation was demonstrated between thrombocyte counts and low density lipids in patients with the severe form of dengue infection [28], suggesting a role for lipid metabolism in the pathogenesis of thrombocytopenia. Therefore, we sought to determine whether low thrombocyte counts were associated with changes in lipid and cytokine profiles of NE cases.…”
Section: Resultsmentioning
confidence: 99%
“…Thrombocyte counts below 50,000 cells/ μ L are considered to be a risk factor for bleeding [25–27]. Recently, a correlation was demonstrated between thrombocyte counts and low density lipids in patients with the severe form of dengue infection [28], suggesting a role for lipid metabolism in the pathogenesis of thrombocytopenia. Therefore, we sought to determine whether low thrombocyte counts were associated with changes in lipid and cytokine profiles of NE cases.…”
Section: Resultsmentioning
confidence: 99%
“…In the same line of evidence, Survana and Rane confirmed later that low levels of cholesterol, HDL, and LDL are associated with severe forms of dengue infection, supporting the hypothesis of van Gorp et al They also observed that VLDL values were different between DF, DHF, and Dengue shock syndrome (DSS) patients, but triglycerides, HDL, and LDL showed no differences (both studies were performed on a pediatric population and they used 1997 WHO dengue guideline for the patient classification in their studies). In contrast Duran's study, which included both adult and pediatric patients (based on 2009 WHO classification for dengue disease), observed a significant decrease in total cholesterol, HDL, and LDL levels, as well as an increase in triglyceride, and VLDL levels, in patients with severe forms of dengue infection.…”
Section: Discussionmentioning
confidence: 84%
“…The last two decades have seen an increasing interest in the study of the possible relationships between the development of severe dengue and changes in circulating lipids . Lipid metabolism is extensively regulated by cytokines during the host response to infection .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A direct link between dengue infection progression and lipid profile changes has been made, so that lipids may be used as predictors of clinical outcome [29]: increased T and HDL and decreased LDL were observed in severe dengue. Recent metabolic and lipid profiling in serum samples from dengue cohorts [30, 31] have reinforced these earlier findings, showing that DENV infection causes temporary changes in metabolites involved in acute inflammatory responses, with major perturbed metabolic pathways including fatty acid biosynthesis, fatty acid beta-oxidation, phospholipid catabolism and steroid hormone pathway, and that progression into DSS is associated with certain metabolites (phosphatidylcholines, diacylglycerol, phosphatidic acid, phosphatidylserine, triglycerides, and diacylglycerophosphoglycerol) that may act in endothelial cell homeostasis and vascular barrier function.…”
Section: Discussionmentioning
confidence: 99%